2008
DOI: 10.1007/s11094-008-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics and useful properties of tarragon (Artemisia dracunculus L.) (review)

Abstract: This review systematizes published data on the chemical composition, biological activities, and uses of the above-ground part of tarragon (Artemisia dracunculus L., Asteraceae family). Analysis of the pharmacological properties of tarragon showed that the most interesting items from the medicinal point of view were its abilities to influence brain function and gastrointestinal tract function and the presence of a broad spectrum of antimicrobial activity. The complexity and variety of the chemical composition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
81
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 7 publications
0
81
0
2
Order By: Relevance
“…There is wide variability in the content of these and other com-321 ponents, depending on growth conditions for the plant at its place 322 or origin, such as soil composition, salinity, and other environmen-323 tal factors (Aglarova et al, 2008 kind that causes DNA fragmentation (Chu et al, 1999 properties observed as a result of the present study.…”
mentioning
confidence: 74%
“…There is wide variability in the content of these and other com-321 ponents, depending on growth conditions for the plant at its place 322 or origin, such as soil composition, salinity, and other environmen-323 tal factors (Aglarova et al, 2008 kind that causes DNA fragmentation (Chu et al, 1999 properties observed as a result of the present study.…”
mentioning
confidence: 74%
“…One of the most common examples is tarragon -A. dracunculus L. It is widespread in the wild across much of Eurasia and North America, and is cultivated for culinary and medicinal purposes. Its essential oils are used as antibacterial agents; dry leaves are added as flavourings for meat and fish (Aglarova et al, 2008;Obolskiy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It also possesses a wide range of health benefits and has therefore been widely used as an herbal medicine [2]. Additionally, a wider range of secondary metabolites (flavonoids, phenyl-propanoids, coumarins, tannins, essential oil) are reported, determining Artemisia dracunculus (A. dracunculus) biological activities and its potential use as a source of plant-derived pharmaceutical chemical entities and complex extracts [3].…”
Section: Introductionmentioning
confidence: 99%